1992
DOI: 10.1016/0378-1097(92)90097-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of peripheral blood monocyte populations in human immunodeficiency virus-1 seropositive patients

Abstract: Monocytes from human immunodeficiency virus (HIV) patients have an increased heterogeneity of phenotype and function. In a study of 120 HIV patients we have demonstrated that they have normal monocyte differential counts but that with progression of the disease an increasing proportion of monocytes show phenotypic and functional evidence for activation or maturation. A proportion of the monocytes are larger, with increased expression of CD11b, HLA‐DR, CD45 and CD16. Concomitantly there was increased expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…An expansion of CD14 + CD16 + monocytes has been observed after HIV-1 infection [10][12] and other inflammatory conditions, while numbers of CD14 ++ monocytes do either not change [11], [13], or decrease slightly [10], in agreement with our observations. It has been assumed that CD14 + CD16 + monocytes are a distinct “proinflammatory” subset of the monocyte lineage [14].…”
Section: Discussionsupporting
confidence: 92%
“…An expansion of CD14 + CD16 + monocytes has been observed after HIV-1 infection [10][12] and other inflammatory conditions, while numbers of CD14 ++ monocytes do either not change [11], [13], or decrease slightly [10], in agreement with our observations. It has been assumed that CD14 + CD16 + monocytes are a distinct “proinflammatory” subset of the monocyte lineage [14].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we determined that NF1 patients with no overt vascular cardiovascular disease have increased numbers of circulating monocytes compared with healthy controls. Further, we identified a population of monocytes in NF1 patients that is characteristic of an activated state, including increased CD16 expression and increased size (35). The finding of increased levels of the proinflammatory cytokines IL-1β and IL-6 in plasma samples from NF1 patients supports the observation that NF1 patients have increased activated monocytes in circulation, given that, in peripheral blood, monocytes are the main producers of IL-1β and IL-6 (56).…”
Section: Figuresupporting
confidence: 63%
“…Analysis of NF1 patient peripheral blood monocytes identified a population of cells that had increased CD16 expression (CD14 dim CD16 bright ) compared with the traditional CD14 + CD16 + monocytes, a population that was not observed in peripheral blood samples from healthy controls ( Figure 6, B and C). Based on the side scatter profile, the population of CD14 dim CD16 bright monocytes, isolated from NF1 patients, was larger in size than other monocyte populations, indicating the cells had increased granularity, a characteristic of monocyte activation (35). Further, May-Grünwald-Giemsa staining of the isolated CD14 dim CD16 bright monocytes demonstrated that the cells were monocytes characterized by an extended cytoplasm and cytoplasmic vacuoles ( Figure 6A).…”
Section: Resultsmentioning
confidence: 98%
“…Reduced clearance of IgG and complement-coated cells in vivo, and reduced Pc-mediated phagocytosis of monocytes and MDM in vitro have been reported [17,18,[32][33][34]. MonoeyteHLA-DR expression in AIDS patients has been reported to be deereased [35], although more recently HLA-DR expression was reported to be increased on a subgroup oflargemonocyLes of HIV ' patients [36], A reduction in FcRIII (CD 16) has been reported in a variety of cells from HIV-infected patients, including peripheral blood lymphocytes and neutrophils, and in cells from bronchoalveolar lavage fluid [37][38][39]. The expression of FeR on monocytes isolated from HIV-infected individuals, however, has not been found to be depressed [40,41].…”
Section: Discussionmentioning
confidence: 99%